Successful outcome of disseminated mucormycosis in a 3-year-old child suffering from acute leukaemia: the role of isavuconazole? A case report - Marjorie Cornu; Bénédicte Bruno; Séverine Loridant; Pauline Navarin; Nadine François; Fanny Lanternier; Elisa Amzallag-Bellenger; François Dubos; Françoise Mazingue; Boualem Sendid (BMC, 2018)
Abstract Background The use of isavuconazole is approved for the management of invasive aspergillosis and mucormycosis, only in adults, as no paediatric pharmacology studies have been reported to date. Very few paediatric cases have been published concerning the use of isavuconazole. Amphotericin B is the only antifungal agent recommended in paediatric mucormycosis, but adverse effects and especially nephrotoxicity, even with the liposomal formulation, could be problematic. In this context, the use of other antifungal molecules active on Mucorales becomes needful. Case presentation We describe a case of mucormycosis with rapid onset dissemination in a 3-year-old girl recently diagnosed with acute lymphocytic leukaemia. She was successfully treated with isavuconazole alone and then in combination with liposomal amphotericin B. Isavuconazole therapy was guided by therapeutic drug monitoring. Conclusions This case offers new perspectives on the potential use of isavuconazole in children with mucormycosis, as an alternative or adjunct to liposomal amphotericin B.